Exposing hidden periodic orbits in scanning force microscopy - Lukas Böttcher; Hannes Wallner; Niklas Kruse; Wolfram Just; Ingo Barke; Jens Starke; Sylvia Speller (Communications Physics)
Abstract The nonlinear interaction between the tip of a scanning probe microscope (SPM) and a sample is manifested in the emergence of bifurcations and unstable branches in the frequency response of a driven cantilever. While extensively investigated theoretically, exploring the unstable branch in an actual SPM experiment is lacking so far, reflecting the broader challenge in studying mechanical nanojunction oscillators under strongly varying external forces. Here we demonstrate experimental tracking of unstable periodic orbits between two saddle-node bifurcation points in the attractive regime, revealing the full set of stationary oscillatory states. This is achieved by a minimally invasive control scheme based on fast adaptive phase extraction and Fourier discretisation of the tip dynamics. Stabilization of unstable branches of oscillating AFM cantilevers opens avenues for novel experimental modes, potentially enabling ultrasensitive surface detection at considerably large amplitudes with minimal tip-surface interaction, new insights in tip-surface interaction mechanisms, as well as new AFM modes enabling arbitrary setpoint choice while inherently avoiding discontinuities.